2023
DOI: 10.1039/d3ra04855a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements of covalent organic frameworks (COFs) as proton conductors under anhydrous conditions for fuel cell applications

Vellaichamy Joseph,
Atsushi Nagai

Abstract: Characteristics of COFs and their proton conducting mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…For anhydrous conduction, porous materials, including MOF, CMP, and POM, have been investigated by using inorganic or organic molecules as proton carriers. These porous materials exhibit proton conductivities of up to 8.2 × 10 –2 S cm –1 . We have demonstrated that stable COFs are robust enough to enable anhydrous proton conduction. …”
Section: Introductionmentioning
confidence: 99%
“…For anhydrous conduction, porous materials, including MOF, CMP, and POM, have been investigated by using inorganic or organic molecules as proton carriers. These porous materials exhibit proton conductivities of up to 8.2 × 10 –2 S cm –1 . We have demonstrated that stable COFs are robust enough to enable anhydrous proton conduction. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of high-performance PEM hold great significance for enhancing performance, reducing costs and industrializing PEMFC. Numerous studies have been conducted on the manufacturing process and material modification of PEM using organic polymers with sulfonic groups, , metal–organic frameworks (MOFs) or coordination polymers (CPs), carbon organic frameworks, , graphene derivatives and their composition materials . Among these materials, crystalline MOFs/CPs and HOFs have attracted increasing attention due to their tunable framework structure, chemical stability, and crystallizability, which can provide an opportunity to explore the relationship between structure and property in terms of proton conduction. However, the grain boundaries resistance and brittleness of crystalline materials limit proton transfer and membrane formation thus hindering practical application.…”
Section: Introductionmentioning
confidence: 99%